BLOOD PRESSURE REDUCTION AFTER CATHETER-BASED RENAL DENERVATION IN PATIENTS WITH CARDIOVASCULAR DISEASE IN THE GLOBAL SYMPLICITY REGISTRY. (June 2022) - Mahfoud, Felix; Schmieder, Roland; Schlaich, Markus; Narkiewicz, Krzysztof; Ruilope, Luis; Williams, Bryan; Fahy, Martin; Mancia, Giuseppe; Bohm, Michael
Abstract : Objective: To evaluate the efficacy of catheter-based renal denervation (RDN) to lower blood pressure (BP) in patients with a history of myocardial infarction or stroke in the Global SYMPLICITY Registry (GSR). Design and method: GSR is a prospective, global, all-comers registry to evaluate the safety and efficacy of catheter-based RDN to lower BP. Patients are enrolled with the intention to receive RDN using either the Symplicity Flex or Symplicity Spyral catheter. Patients are followed at 3, 6, and 12 months, and then annually up to 3 years post-procedure. Office and ambulatory BP are measured at each follow-up and any adverse events are collected. The current post-hoc analysis compares systolic BP (SBP) reduction in patients with and without a history of myocardial infarction as well as with and without history of stroke. Differences in SBP reduction between groups were adjusted for baseline SBP using ANCOVA methods. Results: In March 2021 in GSR, there were 267 patients (10%) with a history of myocardial infarction and 2579 without, and 294 patients with a history of stroke (10%) and 2539 without. Patients with and without a history of myocardial infarction had similar baseline office and ambulatory SBP measurements, whereas patients with a history of stroke had similar office SBP measurements but significantly higher ambulatory SBP (159 ± 22 vs. 154 ± 18, p = 0.005) compared to patients without history of stroke. Office and ambulatory SBP reductions from 6 months to 3 years were similar for patients with and without a history of myocardial infarction after adjusting for differences in baseline SBP (Figure). SBP reductions were also similar for patients with and without a history of stroke except at 6 months for office and ambulatory SBP and at 12 months for ambulatory SBP, when patients with a history of stroke had less BP reduction. Conclusions: Patients with and without a history of stroke or myocardial infarction had similar office and ambulatory SBP reductions after catheter-based RDN, suggesting efficacy of RDN regardless of baseline cardiovascular history.